An Analysis Of Factors Influencing Bpjs Patient Loyalty Based On Customer Satisfaction Theory At Bandung General Hospital Medan - Arum Grahini Kusumadewi; Sri Lestari Ramadhani Nasution; Ermi Girsang; Ali Napiah Nasution (Universitas Pahlawan Tuanku Tambusai, 2025)
Patient loyalty is a critical factor in ensuring the sustainability and competitiveness of hospitals, particularly within health services under the National Health Insurance (JKN) program such as BPJS Kesehatan. According to the 2022 report by the Indonesian Hospital Association (PERSI), the patient retention rate in Indonesian hospitals is only 56%, while the remaining 44% switch to other health facilities due to dissatisfaction with service quality, costs, and accessibility. This phenomenon reflects relatively low patient loyalty, especially among BPJS participants. This study employed a quantitative approach with a cross-sectional design and was conducted at Bandung General Hospital Medan, involving 260 inpatients purposively selected from a total population of 341 patients. Data analysis was performed in three stages: univariate, bivariate using the Chi-Square test, and multivariate using multiple logistic regression. The results revealed four factors that significantly influenced BPJS patient loyalty: satisfaction drivers, emotional response, health worker performance, and relationship quality. Among these, satisfaction drivers emerged as the most dominant factor (OR = 7.611). In contrast, perceived value, expectations, service recovery, and brand image did not show a significant effect. These findings suggest that BPJS patient loyalty is more strongly shaped by direct experiences and emotional interactions during the service process than by external attributes such as brand image or initial expectations.